Citizens defining citizenship: A model grounded in lived experience and its implications for research, policy and practice. (21st June 2021) - MacIntyre, Gillian; Cogan, Nicola; Stewart, Ailsa; Quinn, Neil; O'Connell, Maria; Rowe, Michael
Abstract: Citizenship is gaining currency in health and social care internationally as a way of making sense of the lived experiences of people with major life disruptions who face exclusion, marginalisation and discrimination, but the concept is often contested, poorly defined and understood. This paper charts the development of an empirical model of citizenship within Scotland, UK. A mixed‐method, community‐based participatory research approach using 10 focus groups ( n = 77), concept‐mapping exercises ( n = 45) and statement clarity and relevant ratings ( n = 242) was used to develop a model of citizenship that is grounded in the lived experience of participants, which is absent from current conceptualisations of citizenship. Multidimensional scaling and hierarchical cluster analysis revealed five core domains emerging from our work: 'building relationships', 'autonomy and acceptance', 'access to services and supports', 'shared values and social roles' and 'civic rights and responsibilities' representing the personal meanings of citizenship for participants. We argue that the value of this model is that it is draws upon the personal understandings and experiences of participants who emphasised the 'banal ordinariness' of its core elements. We suggest that the model makes an original contribution by clearly illustrating the practical applicability of citizenship as a concept; thus, enhancing existing theories of citizenship. Our model highlights the interplay between the relational and structural aspects of citizenship and acknowledges the barriers that marginalised groups face in claiming their citizenship rights. It offers a call to action for policy makers and practitioners to set goals that contribute to the social inclusion of those who have experienced major life disruptions.